An ethnomycological approach to land use values in Chukotka - Yamin-Pasternak, Sveta (Études/Inuit/Studies, 2007)
AbstractOnce avoided on both sides of the Bering Strait, wild mushrooms are now considered to be delicious edibles in Chukotka. An important food source, mushroom-gathering is also a recreational activity that cultivates particular relationships between people and the land. In the past, prior to the influences of the mushroom-loving Russian cuisine, the Yupiget of Chukotka regarded mushrooms as “devil ears,” while the Chukchi people largely viewed them as reindeer food, unfit for human consumption. This article examines the transformation in Yupik and Chukchi ideas about mushrooms in the context of a broader ethnohistorical overview. Using the narratives shared by Yupik, Chukchi, and non-indigenous residents of Chukotka, it highlights the role of cultural identity in shaping landscape perceptions, demonstrating how during and after the Soviet period members of each group were finding their own distinct ways of relating to the ecological universe, transformed by new political processes and vast social changes.